Some Uncomfortable Evidence on Slavery and Capitalism - Piqueras , José Antonio (Comparativ, 2021)
Slavery accompanied, even promoted, capitalism from its birth and continued alongside it until the last decades of the 19th century. It remains for us to examine how capitalism and slavery are related. In the historical analysis we have to ask ourselves at every step what kind of slavery we are dealing with and place it within the set of coercive labour modalities that existed in a certain period of history. We have to ask ourselves what kind of capitalism we are dealing with, because capitalism is also subject to evolution. Considering slavery as a labour system, we will analyse the way in which it is linked to capital and (in a later period, as a “second slavery”) slavery is linked to capitalism. Capitalism sometimes created, sometimes subsumed, but always encouraged non-free, non-voluntary forms of work. But, the slavery, conceived as a unique form of coercive labour, has special characteristics within the framework of the hegemony of capital.